2022
DOI: 10.1093/braincomms/fcac093
|View full text |Cite
|
Sign up to set email alerts
|

Auditory experience modulates fronto-parietal theta activity serving fluid intelligence

Abstract: Children who are hard-of-hearing are at risk for developmental language and academic delays compared to children with normal hearing. Some work suggests that high-order cognitive function, including fluid intelligence, may relate to language and academic outcomes in children with hearing loss, but findings in these studies have been mixed and to date there have been no studies of the whole-brain neural dynamics serving fluid intelligence in the context of hearing loss. To this end, this study sought to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…In general, our findings show that ARHL influences theta oscillations at earlier time points on a visual cognitive control task. Our findings align with other studies, both human ( Heinrichs-Graham et al, 2022 ; Ryan et al, 2023 ) and animal ( Johne et al, 2022 ), which have shown that hearing loss modulates oscillatory activity in the theta band. However, adequate comparison of our findings with others is difficult since we used a visual task while most have examined theta activity in relation to auditory tasks, primarily SiN recognition ( Doelling et al, 2014 ; Hyafil et al, 2015 ; Etard and Reichenbach, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In general, our findings show that ARHL influences theta oscillations at earlier time points on a visual cognitive control task. Our findings align with other studies, both human ( Heinrichs-Graham et al, 2022 ; Ryan et al, 2023 ) and animal ( Johne et al, 2022 ), which have shown that hearing loss modulates oscillatory activity in the theta band. However, adequate comparison of our findings with others is difficult since we used a visual task while most have examined theta activity in relation to auditory tasks, primarily SiN recognition ( Doelling et al, 2014 ; Hyafil et al, 2015 ; Etard and Reichenbach, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Prior work has identified the key neural oscillations involved in Gf, which include theta, alpha, and gamma oscillations in frontoparietal regions [25][26][27][28][29][30], with some studies showing that the strength of oscillations in these regions scales with greater cognitive demands and effort [31,32]. Further, oscillatory responses in the PFC and parietal cortices have been shown to support more optimal performance in tasks involving Gf [27,28], thus underscoring the critical role oscillations play in the long-range communication and integration of the distributed networks serving these higher-order cognitive processes [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, we applied HD-tDCS and then collected high-density magnetoencephalography (MEG) during performance of an established abstract reasoning task. This abstract reasoning task was adapted from Raven's Progressive Matrices and has been shown to be tightly linked to classic measures of Gf (Raven & Raven, 2003;Heinrichs-Graham et al, 2022;Taylor et al, 2020Taylor et al, , 2022. Previous studies that stimulated the parietal cortices have shown improved abstract reasoning performance following stimulation compared to the sham condition, although these studies used theta frequency tACS and relatively small samples (Neubauer et al, 2017;Pahor & Jaušovec, 2014).…”
Section: Introductionmentioning
confidence: 99%